FABRICATION OF AN ABUSE DETERRENT AND MICROEMULSION-BASED SUBLINGUAL FILM OF BUPRENORPHINE HYDROCHLORIDE FOR BREAKTHROUGH PAIN MANAGEMENT - MUNDHEY, D.; SAPKAL, N.; DAUD, A. (International Journal of Applied Pharmaceutics, 2020)
Objective: The present research work aims to develop an abuse deterrent rapidly dissolving buprenorphine microemulsion loaded sublingual film for the treatment of breakthrough pain. Methods: The Buprenorphine microemulsion loaded sublingual films were prepared using Capmul MCM C8 (oil), tween 20 (surfactant) and propylene glycol (co-surfactant) with different grades of film-forming polymer (HPMC) using film casting machine. The films were evaluated for in vitro disintegration and dissolution study, tensile strength, folding endurance, content uniformity, surface pH, thickness and weight variation, % loading of buprenorphine microemulsion in sublingual film, scanning electron microscope, ex vivo permeation study, droplet size and polydispersity index, Zeta potential, % moisture content, stability and abuse deterrent potential were evaluated. Results: The optimized film formulation showed desired mechanical properties with minimum disintegration time of 21s and exhibited 34.45 % loading of Buprenorphine microemulsion. Permeation studies through goat sublingual mucosa, indicated 87% Buprenorphine release, through Buprenorphine microemulsion loaded sublingual film, whereas only 30% Buprenorphine release when it was directly added to film without microemulsion strategy. Conclusion: The present study concludes that abuse deterrent and fast acting buprenorphine microemulsion-incorporated sublingual film of buprenorphine HCL and naloxone HCL is a promising alternative to mostly marketed buprenorphine injectable delivery systems and a non-invasive route of administration for breakthrough pain management.